Photoluminescence and Electron Spin Resonance of ilicon Dioxide Crystal with Rutile Structure (Stishovite) - Trukhin, Anatoly; Antuzevics, Andris (Wiley-VCH GmbH, 2018)
An electron spin resonance (ESR) and photoluminescence signal is observed in the as grown single crystal of stishovite indicating the presence of defects in the non‐irradiated sample. The photoluminescence of the as received stishovite single crystals exhibits two main bands – a blue at 3 eV and an UV at 4.75 eV. Luminescence is excited in the range of optical transparency of stishovite (below 8.75 eV) and, therefore, is ascribed to defects. A wide range of decay kinetics under a pulsed excitation is observed. For the blue band besides the exponential decay with a time constant of about 18 μs an additional ms component is revealed. For the UV band besides the fast component with a time constant of 1–3 ns a component with a decay in tens μs is obtained. The main components (18 μs and 1–3 ns) possess a typical intra‐center transition intensity thermal quenching. The effect of the additional slow component is related to the presence of OH groups and/or carbon molecular defects modifying the luminescence center. The additional slow components exhibit wave‐like thermal dependences. Photo‐thermally stimulated creation–destruction of the complex comprising host defect and interstitial modifiers explains the slow luminescence wave‐like thermal dependences.
This work was supported by ERANET MYND. Also, financial support provided by Scientific Research Project for Students and Young Researchers Nr. SJZ/2017/2 realized at the Institute of Solid State Physics, University of Latvia is greatly acknowledged. The authors express our gratitude to R.I. Mashkovtsev for help in ESR signal interpretation. The authors are appreciative to T.I. Dyuzheva, L.M. Lityagina, N.A. Bendeliani for stishovite single crystals and to K. Hubner and H.-J. Fitting for stishovite powder of Barringer Meteor Crater.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; defects; dense silicon dioxides; electron spin resonances; luminescence; stishovites